KEBERAGAMAN TANGGAPAN TERHADAP TEORI PERKEMBANGAN IMAN JAMES W. FOWLER - Branckly Picanussa (IAKN Ambon, 2018)
This article will give information about some responses from the schoolars in relation to Fowler’s theory. Some schoolars gave support for the theory but there are also unsupport to the theory. This article will start with introduction that summaries of Fowler’s book – Stage of Faith: The Psychology of Human deelopment and the Quest for Meaning. Then, continue with some respones. The article will end with some conclusion that I write in closing section.